(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The aim of this study was to examine whether school desk dimensions’ match high school students’ anthropometry. Anthropometric variables (shoulder, elbow, knee and popliteal height, buttock-popliteal length and hip breadth) were measured from randomly selected 328 students who attend public high schools in Mugla/Turkey and school desk dimensions which are in use in corresponding schools were measured to match with anthropometric data. The age range of the children was from 14 to 18 years. Mean, median, standard deviations, minimum values, maximum values, were analyzed statistically. The measured anthropometric dimensions of the students were also compared with those of the school desks in use. The results of the study showed that most of the anthropometric data of students differ significantly and there exists a high mismatch between anthropometric measurements and the school desk that they use.